KEANEKARAGAMAN JENIS BURUNG AIR DI KECAMATAN KAKAS, SULAWESI UTARA - Tiara W. N. Lasantu Tiara W. N. Lasantu; Johny S. Tasirin; Wawan Nurmawan (COCOS, 2020)
ABSTRACT DIVERSITY OF AQUATIC BIRD SPECIES IN KAKAS DISTRICT, NORTH SULAWESI The objectives of the research are to determine the waterbird diversity, community structure and composition. It is also to compare bird communities in the lake and the adjacent forested area. The study was conducted in January to February 2020 in Kakas, Minahasa Regency, North Sulawesi. The water bird communities were observed by count point method along the lake-line and on a transect in the forested area. There were seven observation points along the lake and three at the forested area. The results show that there are 54 species of birds (22 families) with 17 (6 families) species of waterbirds. The community structure and composition in lakes is different to the forests. Species with high important values on the lake are Collocalia esculenta, Egretta garzetta, Ardeola speciosa, Hirundo tahitica, dan Ardea alba (IV 38.74-12.91). The important species in the forested area are Collocalia esculenta, Milvus migrans, Corvus enca, Cinnyris jugularis, dan Zosterops montanus (IV 43.99-12.53). The Shannon-Wiener index is medium 2.25 and the evenness is high 0.70. The community similarity index is low at 0.36. Keywords : Water Birds, Species Diversity, Kakas District